Treatment of cooling water. - Aquaprox (Berlin : Springer, 2009)
Many cooling systems use water as cooling medium. They are found in public buildings, industrial production systems or power plants. Almost every cooling system using water is degraded by deposition, corrosion and microbiological fouling.This book identifies the whole bunch of problems due to water cooling systems and proposes specific solutions to all of them. The authors have an expertise of over 20 years solving cooling water problems. In this book, they advise all practitioners which need to plan, buy or operate cooling systems.